UNDERSTANDING THE EFFECT OF POSTNATAL EXPOSURE TO ANTIBIOTICS ON THE MICROBIOTA-GUT-BRAIN AXIS - Kayyal, Marya (My University, 2018)
Introduction. A 100 trillion bacteria reside in the human gastro-intestinal tract. These microbes are involved in the gut-brain axis. Disruption to their pattern of growth can alter gut-brain communication, and thus health and disease outcomes. Probiotics are being explored for their therapeutic use relative to early-life insults that alter the microbiota, such as antibiotics and stress. In our study, we use a clinically relevant dose of PenicillinV, a beta-lactam antibiotic, and Lactobacillus rhamnosus JB-1, a probiotic, to examine their postnatal effects on long-term immune, nervous, and enteroendocrine status. Methods. BALB/c male and female mice were orally feed, from postnatal day (PND) 14 to 21, twice a day for seven days with either PBS and antibiotics, antibiotics and probiotic, or PBS for both feeding times. For the first experiment, all mice were subjected to behavior tests that measured their anxiety-like and social behavior at PND 70. Fecal samples were collected for microbial diversity analysis 24 hours and 3 weeks after treatment cessation. For the second experiment, mice were sacrificed at PND 22. After decapitation, tissue and serum was collected for analysis of immune, neurochemical, and enteroendocrine markers for both experiments. Results. Antibiotic altered microbial diversity in the short and long term. Male mice exposed to antibiotics showed a decrease in social behavior associated with immune changes. JB-1 attenuated the effects on behavior and immunology. Sex-dependent antibiotic-induced differences in tight junction expression in the brain and ileum were prevented by concurrent JB-1 treatment. Conclusion. Our findings support the principle that early-life perturbations to the gut microbiota can affect other physiological systems in a transient and lasting way. The results also confirm the psychoactive and immune-modulatory function of JB-1 in attenuating immune and behavioral defects induced by antibiotic treatment. The clinical relevance of the antibiotic treatment further shows that the postnatal period is a critical window for microbial, immune, and brain development and is vulnerable to environmental challenges.